Conjugative plasmids in Neisseria gonorrhoeae. - Sox, T E (1978)
A conjugation system initially discovered in beta-lactamase-producing gonococci mobilized small non-selftransmissible R plasmids encoding beta-lactamase (penicillinase) production into other gonococci, Neisseria, and Escherichia coli. This conjugation system was mediated by a separate selftransmissible plasmid of 23.9 X 10(6) daltons, pFA2. Conjugative plasmids capable of mobilizing R plasmids were also found in nearly 8% of the non-penicillinase-producing gonococci. These were similar to pFA2 in size, buoyant density, and restriction endonuclease digest patterns but were less efficient than pFA2 in mobilization of the penicillinase plasmid pFA3. The presence of conjugative plasmids in gonococci isolated before the appearance of penicillinase-producing strains indicates that a conjugation system for plasmid transfer predated the appearance of R plasmids in gonococci.